Tabletop Simulation to Assess Teamwork Competency in OB/GYN Resident Candidates. (October 2016) - Ma, Mary; Kenny, Bronwyn; Feldman, Nathalie; Mann, Stephanie; Nicholas, Cate
Abstract : BACKGROUND: Selecting new residents for an OBGYN training program is a high-stakes undertaking for both candidates and the programs to which they apply. Determining which candidates would work well within their cohort is of paramount importance to the success of a program. In addition, the quality of patient care has been shown to be positively impacted by inter-professional collaboration and well-functioning healthcare teams. METHODS: Mr. Potato Head® tabletop simulation was adapted for use during the UVM OB/GYN Residency Interview Day. Six to 7 candidates were assigned to each team. Candidates were assessed by 2 OBGYN residents who received training on identifying behavioral anchors associated with performance. Results of the team work simulation were included in the holistic review of candidates at the completion of the interview day. RESULTS: Seventy-one percent of candidate respondents reported favorable feedback on a post-interview day survey, describing the activity as a unique experience reflecting the value our program places on teamwork. 30/46 candidates met expectations with 6/30 nearly exceeding expectations. 10/46 candidates were rated as borderline meeting expectations and 6/46 failed to meet baseline expectations. Of the 6 candidates rated as not meeting expectations, 3 (50%) were not ranked in our program. 13/14 interviewers found the Potato Head Simulation to be valuable in their assessment of candidates, with 10/14 reporting a moderate to significant influence. Behavior anchors associated with meeting expectations included good listening skills, treating others with respect, the ability to reflect and be open to feedback. DISCUSSION: Teamwork is a skill set that is difficult to evaluate. Traditional one on one-interview scenarios rarely provide the opportunity for candidates to demonstrate their ability to function within a team. Tabletop Simulation provides a feasible, engaging and well received activity during the interview day to assists programs in evaluating candidate team work skills.